1999
DOI: 10.2337/diacare.22.10.1640
|View full text |Cite
|
Sign up to set email alerts
|

Effects of exercise training on oxygen uptake kinetic responses in women with type 2 diabetes.

Abstract: U ntrained people with type 2 diabetes have been shown to have a re d u c e d VO 2 m a x c o m p a red with nondiabetic people, even in the absence of card i o v a scular disease (1). In addition, it has been re p o rted that VO 2 kinetics are impaired in women with type 2 diabetes (2). The causes of the exercise impairment are unknown, and thus the physiological and clinical significance of these findings warrants further study.VO 2 m a x is the classic measure of overall c a rd i o re s p i r a t o ry fitnes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

18
111
6
4

Year Published

2003
2003
2012
2012

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 129 publications
(139 citation statements)
references
References 6 publications
18
111
6
4
Order By: Relevance
“…The present findings reveal consistently faster _ VO 2 kinetics (i.e., lower MRT) across a wide range of submaximal intensities after training. These data confirm a previous report of a training-induced reduction in the time constant of pulmonary _ VO 2 during exercise, when the _ VO 2 response was assumed to be monoexponential (Brandenburg et al 1999). However, we used a biphasic or triphasic function to characterise this response (Whipp 2009) and showed that the improved mean response time of _ VO 2 , analogous to the finding by Brandenburg et al (1999), was associated with a significant reduction in the time constant of phase 2, as well as a significant reduction in the time constant and amplitude of phase 3 at the highest intensity.…”
Section: Discussionsupporting
confidence: 81%
See 2 more Smart Citations
“…The present findings reveal consistently faster _ VO 2 kinetics (i.e., lower MRT) across a wide range of submaximal intensities after training. These data confirm a previous report of a training-induced reduction in the time constant of pulmonary _ VO 2 during exercise, when the _ VO 2 response was assumed to be monoexponential (Brandenburg et al 1999). However, we used a biphasic or triphasic function to characterise this response (Whipp 2009) and showed that the improved mean response time of _ VO 2 , analogous to the finding by Brandenburg et al (1999), was associated with a significant reduction in the time constant of phase 2, as well as a significant reduction in the time constant and amplitude of phase 3 at the highest intensity.…”
Section: Discussionsupporting
confidence: 81%
“…The rate at which pulmonary oxygen uptake increases during the initial period of exercise ( _ VO 2 kinetics) is slower in young and middle-aged subjects with type 2 diabetes compared with nondiabetic controls (Regensteiner et al 1998;Brandenburg et al 1999;Bauer et al 2007;MacAnaney et al 2011a), although recent data suggests that _ VO 2 kinetics are not impaired in older men with type 2 diabetes compared with aged-matched healthy controls (Wilkerson et al 2011). There is some debate as to whether the source of the slower _ VO 2 kinetic responses observed in young and middle-aged diabetics is due to reduced O 2 delivery and (or) due to lower levels of O 2 extraction.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, it has been reported that increasing the exercise time by one minute on a Balke protocol stress test (which is equivalent to an increase in oxygen consumption of 1.44 ml/kg/min), reduces the risk of overall mortality in people with diabetes by 7.9% (Blair, Kohl III et al 1995;Brandenburg, Reusch et al 1999 Initial improvements of aerobic capacity appear to be more pronounced in individuals with low fitness regardless of obesity level. This was demonstrated in a study that compared women with T2DM to lean and overweight non-diabetic women in a three month exercise intervention (Brandenburg, Reusch et al 1999). The three groups took part in exercise sessions thrice weekly using a treadmill, a c5'cle ergometer or a rowing machine.…”
Section: Aerobic Exercise Trainingmentioning
confidence: 99%
“…Furthermore, many characteristics of skeletal muscle are associated with both low insulin sensitivity and low cardiorespiratory fitness (i.e. decreased capillary density, decreased proportion of Type 1 muscle fibres, higher glycolytic to oxidative enzyme ratio) [8,9,10,11,12,13,14,15].…”
mentioning
confidence: 99%